How does sevuflurane induction, followed by a ketamine maintenance infusion affect intraocular pressure? : establishment of a protocol for paediatric glaucoma examinations under anaesthesia - Van der Walt, Jessica Gwendoline (Department of Anaesthesia, 2016)
Includes bibliographical references